Analysis of Potential Economic Sectors in East Kalimantan Province and its Influence on the Superhub of the National Capital Development of the Archipelago - Mahsun Putra; Muhammad Saleh; Juliansyah Roy (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to identify the leading economic sectors in East Kalimantan Province and analyze their influence on the development of the National Capital of the Archipelago (IKN) as an economic superhub. Using secondary data from 2019–2023, the analysis applies Location Quotient (LQ), Dynamic LQ (DLQ), Shift-Share, and SWOT methods to evaluate the regional economy. Results show that the mining and quarrying sector remains dominant, while agriculture and processing industries demonstrate stable potential for sustainable growth. The study also highlights the urgency of economic diversification, human capital development, and renewable energy as strategic steps to reduce dependence on extractive sectors. The formation of a collaborative blueprint between regional governments, businesses, and communities with the IKN Authority is proposed to strengthen connectivity and economic integration. This research provides critical insights for policy formulation to support East Kalimantan’s transformation as a central player in national development.